QOL-30. Positive Effects of a psychological preparation program for MRI in children with cognitive issues – how to best meet the patients' needs. (3rd June 2022) - Weiler-Wichtl, Liesa Josephine; Fries, Jonathan; Fohn-Erhold, Verena; Schwarzinger, Agathe; Holzer, Angelika; Pletschko, Thomas; Furtner, Julia; Preyer, Daniela; Baer, Paul; Slavc, Irene; Peyrl, Andreas; Azizi, Amedeo; et al.
Abstract: BACKGROUND: A growing body of evidence has supported alternatives to sedation and general anesthesia for increasing treatment compliance of children during MRI examinations. Particularities in children with a brain tumor (frequency of examinations, neuropsychological deficits (attention, memory)) have a significant impact on methods of treatment and are given special consideration in this study. OBJECTIVE: The aim of the present study was to (1) evaluate the effectiveness of an MRI training program and to investigate the moderating factors for successful MRI examination for a group of young patients with pediatric brain tumors and/or NF1 and (2) to examine the effect of the training on the patient's well-being. METHODS: A total of 87 in the retrospective analyses (Study 1) and a subgroup of 17 patients in the prospective analyses (Study 2, ClinicalTrials.gov: NCT04474678) of the neuro-oncology unit with a mean age of 6.83 years underwent a two-step program to prepare children for MRI, including an in vitro strategy training inside the scanner and were recorded using a process-oriented screening. RESULTS: 81 % of the children who had received MRI training managed to successfully undergo the MRI scan. Hence, the rate of successful MRI examinations without anesthesia was almost five times as high in the group that received MRI training compared to the group that did not. Memory, attentional difficulties and hyperactivity were significant neuropsychological moderators for successful or unsuccessful scanning. Furthermore, the training was effective in improving the psychological well-being of the patients. CONCLUSION: Based on the results, the MRI training is an effective alternative to sedation of young patients for MRI examinations and a promising tool for improving patient well-being related to the diagnostic procedure. However, the intervention needs to be customized according to the children's individual neuropsychological difficulties, which requires specialized psychological staff and an interdisciplinary approach.